(untitled) - Nguyễn, Trung Vệt (Netherlands, 1999)
The mainof this thesis is to assess the applicability of UASB process for treating RLP wastewater and the feasibility of some adequate post-treatment processes for the effluent of the anaerobic treatment process.
Keywords: Wastewater treatment and reuse,Xử lý nước thải và tái sử dụng